Critical Success Factors for Knowledge Transfer via a Malaysian Government Education Website - Nurdiana Azizan; Ross Smith; Vanessa Cooper,; Noraizah Abu Bakar (Universiti Sains Islam Malaysia, 2024)
This paper presents the critical success factors (CSFs) for knowledge transfer via a Malaysian government education website, from the perspective of provider. The research explores CSFs from a case study at Department of Education in Malaysia that is known as MASED. The research adapted Szulanski’s four stages, namely initiation, implementation, ramp-up and integration that is known as intra-organisational knowledge transfer model to identify CSFs for knowledge transfer via government education website. The research has employed an interpretive case study approach, applying qualitative data capture and analysis methods. Primary data were derived from the interviews with 15 government officers that are involved in the development and management of government education website. Qualitative content analysis by inductive approach was used as analysis technique. From the analysis, 14 CSFs were identified and grouped into six themes, namely management role, user focus, employee focus, content focus, technology focus and organisational focus. Then these CSFs were validated in a focus group with the same 15 respondents to finalise the CSFs for knowledge transfer via Malaysian government education website. This research used a single study of one government agency in Malaysia. The research provides practical guidance to practitioners particularly to the government website providers. In order to increase the level of knowledge transfer to users, the CSFs can support government website providers in taking strategic decisions related to the internal operation of their website’s content development and delivery activities.